KAJIAN ILMU PENGETAHUAN SOSIAL DAN ILMU SOSIAL SEBAGAI BAHAN MATERI IPS UNTUK SEKOLAH DASAR - Zurahmah Zainuddin; Agustang Agustang; Ilham Laman (LP2M Institut Agama Islam (IAI) Muhammadiyah Sinjai, 2022)
Social studies and social sciences are interconnected. Both are related to basic human needs, then these basic needs can be achieved by basic human activities. Basic human activities include education, production and consumption, organization and government, protection and maintenance, aesthetics and recreation. All of them build social sciences. In the social sciences, it is classified into fields of science which include, among others, history, economics, political science, law, geography, anthropology, and social psychology. And in it there are facts, concepts, generalizations that were developed to build Social Sciences (IPS).